Skrining Kesehatan Lanjut Usia Melalui Program Edukasic USK - Ardia Putra; Nurhasanah Nurhasanah; Nurul Hadi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
This community service activity is planned to be held in Cot Preh Village, Kuta Baroe District, Aceh Besar. This gampong (village) is one of the gampongs located in the working area of the Lambaro Health Center, which has access to and good reception of health information. In addition, health cadres, village heads, and Cot Preh village officials fully support the health education programs provided by the community service team. This service activity is one of the preventive and promotive actions of several community health empowerment service efforts. The health empowerment activities focus on the elderly group regarding the